Building Islamic Ideology From Historical Studies : From Pesantren To Parliamentary Leadership - Hasan, Yafis Alfian (Ahlika: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Political parties are the axis of the democratic movement in a country. The urgency of ideology in political parties is very important in determining the party's future policies and decisions and strengthening the party's identity in the diversity of society. The emergence of ideology in people's lives gives its own style and has an impact on modern democracy. This study uses a qualitative descriptive approach. The results of the study show that Islamic ideology has colored democratic life by integrating Islamic values in the law and laws of the republic. Islamic boarding schools become institutions that supervise the Islamic community and educate and foster Islamic ideology and a sense of nationalism towards the republic. Behind that, Islamic boarding schools also produce the next generation in sustainability. The emergence of figures during the independence period is an example for Muslims today. Abstrak: Partai politik menjadi poros dalam gerakan demokrasi di suatu negara. Urgensi ideologi dalam partai politik sangat penting dalam menentukan kebijakan, keputusan masa depan partai dan memperkuat identitas partai dalam keberagaman masyarakat. Munculnya ideologi dalam kehidupan masyarakat memberikan gayanya sendiri dan berdampak pada demokrasi modern. Penelitian ini menggunakan pendekatan deskriptif kualitatif. hasil penelitian menunjukkan ideologi Islam telah mewarnai kehidupan demokrasi dengan mengintegrasikan nilai-nilai Islam dalam hukum dan hukum republik. Pesantren menjadi lembaga yang mengawasi komunitas Islam dan mendidik serta menumbuhkan ideologi Islam dan rasa nasionalisme terhadap republik. Di balik itu, Pesantren juga menghasilkan generasi penerus dalam keberlanjutan. Munculnya tokoh-tokoh pada masa kemerdekaan menjadi contoh bagi umat Islam saat ini.